(3GdeLehY GdeMjW HGdJcdjas - (3Ydj Hf CMeO Hf eMeO Hf Ydj Hf neoqJhjI, CHh GdMSf GdhGMOj,J (B468 (3g` s
(3ChdgG (B:s
(3jHOC HHGH ai Led GdJcdja s
(3BNQgG (B:s
(3hgPg LedI eeG ChQOg Je GdLRA GdJGSY ef cJGH GdeMjW HGdJcdja HYhf Gddg hefg hHJeGeg Je GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B255 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B26 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B692s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B_ (3GdNRGfI GdJjehQjI (B((3YbGFO (B357) s
Keywords: (3GdJhMjO hGdedd hGdfMds